Molecular adaptations in MMP genes support lung elasticity and diving adaptations in cetaceans - Ya Zhang; Wenjun Lv; Wen Yan; Boxiong Guo; Guang Yang; Wenhua Ren (BMC Genomics, 2025)
Abstract Cetaceans are a unique group of marine mammals that have evolved from terrestrial to fully aquatic life. During diving, they experience extreme physiological challenges, including lung collapse, limited gas exchange, and the risk of decompression-related injuries. The matrix metalloproteinase (MMP) gene family plays a central role in extracellular matrix (ECM) remodeling, vascular repair, and inflammatory responses, and is also involved in the formation and maintenance of elastic fibers—key components that contribute to lung elasticity. Enhanced lung elasticity is thought to facilitate reversible lung collapse and efficient blood shift during dives, ultimately reducing nitrogen uptake and the potential risk of decompression sickness (DCS). In this study, we analyzed 1,058 genes from 46 species, focusing on cetaceans and other diving marine mammals, with terrestrial mammals as a reference group. Our results reveal that the MMP gene family has undergone positive selection in cetaceans, with nine genes exhibiting accelerated evolution. Notably, we identified a cetacean-specific N319S mutation in the Fibronectin type-II domain of MMP9, which impairs collagen-binding and degradation, as confirmed by Western blot analysis. Mass spectrometry further revealed an increased number of post-translational modifications in cetacean MMP9 compared to terrestrial mammals, with several modifications overlapping the mutation sites. These findings suggest that adaptive changes in MMPs may enhance elastic fiber dynamics and vascular remodeling in cetaceans, contributing to physiological adaptations such as improved lung compliance and resilience to diving-related stress, including reduced susceptibility to DCS.